Financing entrepreneurship and innovation in emerging markets - Casanova, Lourdes; Cornelius, Peter 1960-; Dutta, Soumitra (Academic Press, an imprint of Elsevier, 2018)
Financing Entrepreneurship and Innovation in Emerging Markets offers an original perspective on the links between macro data on innovation, data on micro-entrepreneurial processes and venture capital supply. The authors synthesize two disparate fields of research and thinking-innovation and entrepreneurship and economics-to illuminate how domestic companies compete and the business environment in which entrepreneurial firms operate. Its broad scope and firm linkages between processes at different levels leapfrogs research topics. For those investigating entrepreneurship and innovation in the early stages of economic development, this book demonstrates how micro and macro foundations of productivity, and hence economic growth and development, are inextricably intertwined
Includes bibliographical references and index
Keywords: BUSINESS & ECONOMICS / Industries / General; Entrepreneurship; New business enterprises; Innovation; Kapitalmarkt; Emerging Market; Schwellenländer